2002
DOI: 10.1124/jpet.301.3.1179
|View full text |Cite
|
Sign up to set email alerts
|

Functional Selectivity of Dopamine Receptor Agonists. II. Actions of Dihydrexidine in D2LReceptor-Transfected MN9D Cells and Pituitary Lactotrophs

Abstract: D 2 -like dopamine receptors mediate functional changes via activation of inhibitory G proteins, including those that affect adenylate cyclase activity, and potassium and calcium channels. Although it is assumed that the binding of a drug to a single isoform of a D 2 -like receptor will cause similar changes in all receptor-mediated functions, it has been demonstrated in brain that the dopamine agonists dihydrexidine (DHX) and N-npropyl-DHX are "functionally selective". The current study explores the underlyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
63
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 65 publications
1
63
0
Order By: Relevance
“…MAP kinase and GIRK channel activation) (Gay et al, 2004). However, in an other study SNPA was determined to be a partial agonist with regard to cAMP signaling (Kilts et al, 2002). This discrepancy could arise from spare receptor effects in the heterologous expression system where SNPA was observed to be a full agonist.…”
Section: Discussionmentioning
confidence: 98%
“…MAP kinase and GIRK channel activation) (Gay et al, 2004). However, in an other study SNPA was determined to be a partial agonist with regard to cAMP signaling (Kilts et al, 2002). This discrepancy could arise from spare receptor effects in the heterologous expression system where SNPA was observed to be a full agonist.…”
Section: Discussionmentioning
confidence: 98%
“…The first molecular description of this phenomenon ascribed this effect to the stabilization of different receptor active states by different agonists (Kenakin and Morgan, 1989;Kenakin, 1995). The ability of agonists to choose signaling pathways has been given a number of names ("stimulus trafficking," Kenakin, 1995; "functional selectivity," Lawler et al, 1999;Kilts et al, 2002;Shapiro et al, 2003;"functional dissociation," Whistler and von Zastrow, 1999; "biased inhibition," Kudlacek et al, 2002;"differential engagement," Manning, 2002); the term "biased signaling" was introduced by Jarpe et al (1998) and is favored as a general descriptor of the effect. It is worth considering the present place of this idea in new drug discovery.…”
Section: Introductionmentioning
confidence: 99%
“…As GPCRs, D 2 receptors mediate these downstream effectors via activation of G␣ i/o and various G␤␥ subunits, as well as other proteins such as G protein-coupled receptor kinases. Studies over the last decade have shown that some D 2 ligands can cause functionally selective signaling both in vivo and in vitro (Lawler et al, 1999;Kilts et al, 2002;Mottola et al, 2002;Shapiro et al, 2003). In the striatum, the dopamine receptor agonist dihydrexidine (DHX) was able to inhibit adenylate cyclase activity with the same maximal intrinsic activity as quinpirole, a prototypical D 2 receptor agonist.…”
mentioning
confidence: 99%